Design and Development of a Village Information System with the Rapid Application Development Method - Lubis, Melza Alzira; Tarigan, Siti Jamillah Br (Karya Techno Solusindo, 2024)
Abstract: Tandem Hulu I Village is one of the villages located in the Hamparan Perak District area, North Sumatra, which was initially just an oil palm plantation area in which man workers from the oil palm plantation land were made into residence and finell the workers inhabit the area. From the past until now. Tandem Hulu I Village has always been the focus of attention in every discussion about the regional government system. because the village is a subsystem of the regional government system. This system was built using the RAD (Rapid Application Developmet) method, which was superior capabilities to previously developed components and can be used again in the development of new system. Researchers chose this method because it is considered easier to apply in system development that focuses on each development requirement. The system designed relles on internet technology to be accessible by users and admins the process Keywords: Information System, Village Information System, Rapid Application Development Anggiawan, D. D., Pandie, E. S. Y., Kom, S., Kom, M., Boru, M., & Kom, M. (2018). SISTEM INFORMASI PELAYANAN PUBLIK KELURAHAN BAKUNASE KOTA KUPANG UNTUK PENINGKATAN KUALITAS PELAYANAN BERBASIS WEB. 6. Arifin, M. S., Rachmat, Z., Laratmase, P., Muniarty, P., Sudirjo, F., Ilyas, M., Purba, S., Pratiwi, A. M., Sinaga, H., & Aguilika, D. (2023). Sistem Informasi Manajemen. Global Eksekutif Teknologi. Fanani, M. I., & Setiawan, E. (2022). PERANCANGAN ARSITEKTUR SISTEM INFORMASI SEKOLAH MENGGUNAKAN METODE TOGAF ADM PADA SMKN 1 KEMLAGI DESIGN OF SCHOOL INFORMATION SYSTEMS USING THE TOGAF ADM METHOD AT SMKN. Jurnal SimanteC Vol, 10(2). Marpaung, R. (2020). Analisis Peranan Sistem Informasi Akuntansi dalam Meningkatkan Pengendalian Internal pada Rumah Sakit Bhayangkara Anton Soejarwo. MABIS, 11(2). Mawardi, M. I., Budianto, E. W. H., & Dewi, N. D. T. (2023). Bank Tabungan Pensiunan Nasional (BTPN) Syariah dan Konvensional: Studi Pustaka (Library Research) dan Bibliometrik VOSviewer. Melinda, M., Borman, R. I., & Susanto, E. R. (2018). Rancang Bangun Sistem Informasi Publik Berbasis Web (Studi Kasus: Desa Durian Kecamatan Padang Cermin Kabupaten Pesawaran). Jurnal Tekno Kompak, 11(1), 1–4. Mustanir, A. (2019). Pemberdayaan Badan Usaha Milik Desa Melalui Kelompok Ekonomi Kewirausahaan Secara Partisipatif. Open Science Framework. https://doi.org/10.31219/osf.io/pwb2g Oktaviani, L., & Ayu, M. (2021). Pengembangan sistem informasi sekolah berbasis web dua bahasa SMA Muhammadiyah Gading Rejo. Jurnal Pengabdian Pada Masyarakat, 6(2), 437–444. Prehanto, D. R., Kom, S., & Kom, M. (2020). Buku Ajar Konsep Sistem Informasi. Scopindo Media Pustaka. Rauf, E. U. T. (2017). ANALISIS SISTEM INFORMASI MANAJEMEN DALAM MENINGKATKAN KUALITAS PELAYANAN DI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS SABURAI BANDAR LAMPUNG. Jurnal Kebijakan Dan Pelayanan Publik, 3(2). Ridwan, M., Widiastiwi, Y., Zaidiah, A., Purabaya, R. H., Isnainiyah, I. N., Ardilla, Y., Krisnanik, E., Yuliana, R., Arta, I. P. S., & Ningsih, S. (2021). Sistem informasi manajemen. Penerbit Widina.